Implementation of the CultIS Platform at the Sofia University Library “St. Kliment Ohridski”: Challenges, Results, and Perspectives - Yavrukova, Bilyana; Goynov, Maxim; Paneva-Marinova, Desislava (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2026)
The Sofia University Library is the largest academic library in Bulgaria and one of the leading libraries in the country. The paper presents a case study on the implementation of CultIS – a web-based software platform for intelligent digital management and presentation of large datasets and knowledge in the fields of culture, humanities, and social sciences, carefully preserved by the library for many years. The process from both technological and library perspectives will be presented, examining the challenges the team overcame, and the decisions made at each stage. Like any modern library, the Sofia University Library actively provides opportunities for secondary publishing, which are made possible by implementing the platform and integrating it with the Bulgarian Portal for Open Science. The results after one year of using the platform will be presented.
Keywords: Digital Library; Platform Migration; CultIS; Sofia University Library; Open Science; Metadata Management; Digital Preservation